Immortal - Golden, Christopher; Holder, Nancy; Whedon, Joss. (New York : Pocket Books, 2000)
Buffy is challenged by a vampire who is immortal.
"An original novel based on the hit TV series created by Joss Whedon".
"Pocket Books paperback"--T.p. verso.
Keywords: Vampires -- Fiction; California -- Fiction; Vampires -- Fiction; Vampires -- Fiction; California -- Fiction; California -- Fiction